ภูมิปัญญาท้องถิ่นของชาวสวนทุเรียนในพื้นที่ตำบลบางกร่าง อำเภอเมืองนนทบุรี จังหวัดนนทบุรี - สวัสดี อักษร (Academic Journal Phranakhon Rajabhat University, 2017)
This research aims to 1) study the local wisdom of durian gardeners in Bang Krang sub-district, Nonthaburi province and 2) study the way to transfer the knowledge in durian gardening of gardeners in Bang Krang sub-district, Nonthaburi province. The interviewees included in the research consisted of two agricultural specialists and four experts in durian gardening in Bang Krang sub-district. The in-depth interview was employed to collect the data. The content data was used to analyze and the descriptive analysis results were presented. The research results revealed: 1. The local wisdom of durian gardeners in Bang Krang sub-district has been inherited from ancient times.The strength of this area was that fertility of the mineral soil which has been suitable for durian gardening. Planting by lifting the groove about 80 centimeters high has been popular. The hole on the ditch was dug about 50 centimeters deep. Fertilizer was firstly put at the bottom of the hole. Next, durians that were nursed for about a year were put into the hole. Putting fertilizer, trimming branches and watering durian trees every two days were taken. For watering durian trees, watering vessels should be used to take the water from the bottom of the garden groove, filled with minerals from mud. Taking care should be done closely until fruit out. 2. The knowledge in durian gardening of gardeners in Bang Krang sub-district, Nonthaburi province was transferred as follows: 1) The learning center was founded for training, demonstrating, explaining and answering visitors’ questions, including the learning-exchanging among visitors from other areas and 2) The family members or local people were transferred individually by real-practicing; from the area preparing, planting, care-taking to harvesting crops. If having any doubts, inquiry can be presented directly at the practicing places and the further explanations were also suggested.